EFEKTIVITAS IMPLEMENTASI KURIKULUM INDONESIA DI SEKOLAH INDONESIA KUALA LUMPUR (SIKL) DAN KURIKULUM MERDEKA DI INDONESIA - Syukri Syukri; Nurul Azizah binti Hamdan; Muh Rezky; Nur Fadhila Al-Ilmiah MS; Sri Yuningrum Suningrat; SK Ahmad Ali Usman Haktab (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2023)
This study aims to describe the effectiveness of implementing the Indonesian Curriculum at Sekolah Indonesia Kuala Lumpur (SIKL) and to compare it with the implementation of the Merdeka Curriculum in Indonesia. The background of this research stems from the need to understand how the national curriculum is applied in the context of Indonesian schools abroad, as well as its alignment with the latest curriculum approach currently implemented in Indonesia. This study employs a descriptive qualitative method, with data collected through interviews, observations, and document studies. The results indicate that the implementation of the Indonesian Curriculum at SIKL is fairly effective, characterized by the adaptation of learning to international contexts and the needs of multicultural students. Meanwhile, the implementation of the Merdeka Curriculum in Indonesia shows a high level of flexibility in project-based learning development and the strengthening of the Pancasila Student Profile. The comparison of the two curriculum reveals that the school context is a determining factor in implementation effectiveness. This study emphasizes the importance of policy support, teacher readiness, and learning facilities in enhancing successful curriculum implementation.